2020
DOI: 10.1177/1948550619884564
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons Across Dimensions, People, and Time: On the Primacy of Social Comparison in Self-Evaluations

Abstract: People often consider how their performance in one domain compares to their performance in other domains, the performance of other people, and their past performance (i.e., dimensional, social, and temporal comparison). The present research is the first to test whether social comparisons have a significantly larger effect on self-evaluations than dimensional and temporal comparisons. Study 1 participants received downward versus upward dimensional, social, and temporal comparison feedback ( N = 393). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Results showed that both social and dimensional comparisons produced contrast effects on self-evaluations (i.e., downward comparisons increased self-evaluations), and that social comparisons elicited more robust effects. These findings conceptually replicate experimental studies in academic contexts (e.g., Strickhouser & Zell, 2015;Zell & Strickhouser, 2020) and extend such findings to health-related contexts.…”
Section: Dimensional Comparisons In Health Behavior Contextssupporting
confidence: 83%
“…Results showed that both social and dimensional comparisons produced contrast effects on self-evaluations (i.e., downward comparisons increased self-evaluations), and that social comparisons elicited more robust effects. These findings conceptually replicate experimental studies in academic contexts (e.g., Strickhouser & Zell, 2015;Zell & Strickhouser, 2020) and extend such findings to health-related contexts.…”
Section: Dimensional Comparisons In Health Behavior Contextssupporting
confidence: 83%
“…This implies that people with little experience must use proof from other domains in their life, such as how well they can handle relationships in general, or by observing other people interact with a dog (vicarious learning). Another way of estimating one's own ability is by making social comparisons [22], which are highly important in the process of self-evaluation [23]. In social comparisons, people compare their own ability with the abilities of other specific people (e.g., their neighbors) or in a more generalized manner (e.g., a constructed mental image of dog-owners in general).…”
Section: Introductionmentioning
confidence: 99%
“…In line with the I/E model studies, the social comparison effects exceeded the dimensional comparison effects. The temporal comparison effects, if examined, were only sometimes significant (Müller-Kalthoff et al, 2017;Wolff, Helm, Zimmermann, et al, 2018; but see; Zell & Strickhouser, 2020).…”
Section: F I G U R Ementioning
confidence: 98%
“…In line with the I/E model studies, the social comparison effects exceeded the dimensional comparison effects. The temporal comparison effects, if examined, were only sometimes significant (Müller‐Kalthoff et al., 2017; Wolff, Helm, Zimmermann, et al., 2018; but see; Zell & Strickhouser, 2020). Nonetheless, the experimental findings overall further substantiated the assumption that social, dimensional, and temporal comparisons have causal and additive effects on students' domain‐specific self‐concepts.…”
Section: Dimensional Comparison Effectsmentioning
confidence: 99%